2005
DOI: 10.1074/jbc.m502024200
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of Yeast Actin Polymerization by Yeast Arp2/3 Complex Does Not Require an Arp2/3-activating Protein

Abstract: The Arp2/3 complex creates filament branches leading to an enhancement in the rate of actin polymerization. Work with Arp complexes from different sources indicated that it was inactive by itself, required an activating factor such as the Wiskott-Aldrich syndrome protein (WASP), and might exhibit a preference for ATP or ADP-P i actin. However, with yeast actin, P i release is almost concurrent with polymerization, eliminating the presence of an ADP-P i cap. We thus investigated the ability of the yeast Arp2/3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 43 publications
(52 reference statements)
3
33
0
Order By: Relevance
“…S1 A and B; Movie S1), monomeric actin (sparsely labeled with the green-emitting dye Alexa Fluor 488) and the VCA portion of S. cerevisiae Wiskott-Aldrich syndrom protein (WASp/Las17; unlabeled), and observed filament assembly by total internal reflection fluorescence (TIRF) microscopy. As previously seen using labeled actin and unlabeled Arp2/3 complex, we observed formation of branched filament networks (4,5,7,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and branches rarely if ever dissociated over tens of minutes (26). We saw that 90% (143/160) of branch junctions displayed well-defined spots of orange Arp2/3 complex fluorescence that typically persisted for tens or hundreds of seconds (Fig.…”
Section: Individual Arp2/3 Complexes Bind the Sides Of Preexisting Actinsupporting
confidence: 51%
“…S1 A and B; Movie S1), monomeric actin (sparsely labeled with the green-emitting dye Alexa Fluor 488) and the VCA portion of S. cerevisiae Wiskott-Aldrich syndrom protein (WASp/Las17; unlabeled), and observed filament assembly by total internal reflection fluorescence (TIRF) microscopy. As previously seen using labeled actin and unlabeled Arp2/3 complex, we observed formation of branched filament networks (4,5,7,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and branches rarely if ever dissociated over tens of minutes (26). We saw that 90% (143/160) of branch junctions displayed well-defined spots of orange Arp2/3 complex fluorescence that typically persisted for tens or hundreds of seconds (Fig.…”
Section: Individual Arp2/3 Complexes Bind the Sides Of Preexisting Actinsupporting
confidence: 51%
“…Our cross-linking experiments showed that, even without WASP, a small fraction of the complex adopts the short-pitch conformation (Fig. 2 A and C), consistent with the weak NPF-independent activity of the budding yeast complex (13,38). Therefore, we reasoned that cross-linking could be used to trap a fraction of the complex in the short-pitch conformation to test its influence on nucleation activity directly.…”
Section: Resultsmentioning
confidence: 99%
“…If such a "direct-coupling" mechanism is valid one might intuitively expect mutations that modify the rates of F-actin polymerization to exhibit proportional changes in mitochondrial mobility. The act1-v159n mutant is known to stabilize F-actin and thereby increase the forward rate of F-actin assembly while decreasing the disassembly rate (21). Our experiments on this mutant show an enhancement of the long-time diffusion coefficient for length scales ≥0.78 μm (see Fig.…”
Section: Discussionmentioning
confidence: 64%
“…The act1-v159n protein is thought to stabilize F-actin by enhancing the forward polymerization rate. For example, Wen et al observed in vitro enhanced polymerization rates of yeast act1-v159n protein in the presence of the actin filament nucleation complex Arp2∕3 (21). At the elevated temperature of 36°C we observe an enhancement of the dynamics for act1-V159N in comparison to wild-type mitochondria for d G ≥ 0.79 μm.…”
mentioning
confidence: 82%